PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP MINAT BELAJAR SISWA KELAS VII MTs AL MUSTAQIM - Nurul Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aimed to determine the effect of the Contextual Teaching and Learning (CTL) model on students’ learning interest at MTs Al Mustaqim. The background of this study was the low learning interest among students caused by conventional teaching methods that fail to link learning materials to real-life contexts. This quantitative study employed a one-group pretest–posttest design involving one experimental class selected using purposive sampling. Data were collected through a learning interest questionnaire and observation sheets. The results indicated that CTL implementation was very effective, achieving 85%–87.5% of expected learning activities. The paired sample t-test showed a significant difference in learning interest before and after the intervention (p < 0.001). Students’ learning interest improved to the “sufficiently interested” category after applying CTL. Thus, the CTL model effectively enhances students’ learning interest in mathematics, making learning more contextual and meaningful.